2023
DOI: 10.1158/1055-9965.epi-22-1154
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Psychiatric Correlates of Cancer among Homeless and Unstably Housed Veterans in the VA Health Care System

Abstract: Background: This study examined the incidence and correlates of cancer among homeless and unstably housed (HUH) veterans as compared to stably housed (SH) veterans. Methods: Using VA administrative data from 564,563 HUH and 5,213,820 SH veterans in 2013 and 2014, we examined the types and stages of 69 different types of cancer diagnosed among HUH and SH veterans. Sociodemographic and psychiatric characteristics associated with cancer were also examined. Results: The one-year incidence rate of cancer was 21.5% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…Housing Status, Cancer Care, and Associated Outcomes Among US Veterans metastatic colorectal cancer than patients with housing (22% vs 19%), but they were diagnosed at similar lung and breast cancer stages. Although this finding is consistent with other VA studies, 20 it differs from other settings. For example, a study from the Boston Health Care for the Homeless Program reported that greater than 40% of colorectal cancers in patients experiencing homelessness were metastatic on presentation (compared with <20% of patients with housing) and almost 70% of breast cancers in these patients were locally advanced on presentation.…”
Section: Jama Network Open | Equity Diversity and Inclusionsupporting
confidence: 91%
“…Housing Status, Cancer Care, and Associated Outcomes Among US Veterans metastatic colorectal cancer than patients with housing (22% vs 19%), but they were diagnosed at similar lung and breast cancer stages. Although this finding is consistent with other VA studies, 20 it differs from other settings. For example, a study from the Boston Health Care for the Homeless Program reported that greater than 40% of colorectal cancers in patients experiencing homelessness were metastatic on presentation (compared with <20% of patients with housing) and almost 70% of breast cancers in these patients were locally advanced on presentation.…”
Section: Jama Network Open | Equity Diversity and Inclusionsupporting
confidence: 91%